Answers in the pages - Levithan, David (Alfred A. Knopf, 2022)
Donovan thinks nothing of it when he leaves his copy of "The Adventurers" on the kitchen table one day, but soon his mother and other parents are lobbying to have it banned because the book's main characters are gay. Donovan doesn't think there's anything wrong with that, and he doesn't really know if the two boys fall in love at the end or not, so he's confused about the parents' complaint about inappropriate content. Soon, the whole community is in an uproar over the book, and a book challenge is raised. Together with his classmates, Donovan helps stand up for the book and the right for young people to be able to read what they want.